2009
DOI: 10.1021/jp9005058
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Renormalization Group Coarse-Graining of Electrolyte Solutions: Application to Aqueous NaCl and KCl

Abstract: Simplified, yet accurate, coarse-grained models are needed to explore the behavior of complex biological systems by means of Molecular Dynamics (MD) simulations, because many interesting processes occur at long time scales and large length scales that are not amenable to studies by atomistic simulations. The aqueous salt buffer provides an important contribution to the structure and function of biological molecules. While in many simplified models both water and salt are treated as a continuous medium, it is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 38 publications
(78 reference statements)
2
97
0
Order By: Relevance
“…Solvent-mediated interionic effective potentials, taking into account the molecular structure of the solvent and specific short-range interactions, can be built from atomistic molecular dynamics simulations as it was done in a number of previous studies. 1,5,8,29 Hess et al 9 investigated concentration dependence of NaCl ion-ion effective potentials constructed from atomistic simulations. It was shown that the main part of this dependence can be attributed to the change of the effective dielectric permittivity, which decreases with the ion concentration, affecting the long-range behaviour of the effective potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent-mediated interionic effective potentials, taking into account the molecular structure of the solvent and specific short-range interactions, can be built from atomistic molecular dynamics simulations as it was done in a number of previous studies. 1,5,8,29 Hess et al 9 investigated concentration dependence of NaCl ion-ion effective potentials constructed from atomistic simulations. It was shown that the main part of this dependence can be attributed to the change of the effective dielectric permittivity, which decreases with the ion concentration, affecting the long-range behaviour of the effective potentials.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the Force Matching or Multi-scale coarse graining scheme, other structure-based methods provide CG interactions that reproduce pre-defined target structure properties-often a set of radial distribution functions [77][78][79][80][81][82][83][84][85][86][87][88][89]. This means that the many-body PMF (Equations (6) and (7)) is replaced as a target by a set of simpler structural correlation functions.…”
Section: Boltzmann-inversion Based Methodsmentioning
confidence: 99%
“…The disadvantage of IMC on the other hand is a high computational cost and problems with numerical stability; for a detailed comparison see Reference [116]. Related to IMC, there are several other recent developments, e.g., a molecular renormalization group approach [85][86][87] or an approach that relies on relative entropies [96][97][98] (which will be discussed in more detail below). While the above structure-based methods by construction reproduce exactly, within the error of the numerical procedure, the local pair structures and thus are well-suited to the reinsertion of atomistic coordinates, it can be expected a priori that they will not be equally well suited to the reproduction of thermodynamic properties (pressure, phase behavior, etc.)…”
Section: Boltzmann-inversion Based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different ions have different hydration shells in thickness and stability. According to molecular dynamics (MD) simulations using explicit water models, [11][12][13][14][15] small cations cannot approach each other up to contact position: there are always water molecules between two cations (large anions do not seem to produce this effect). Cation-anion pairs, on the other hand, produce the opposite behavior: due to their strong electrostatic attraction, they can approach each other closer than the sum of the ionic radii.…”
mentioning
confidence: 99%